Primary retroperitoneal nodal endometrioid carcinoma associated with Lynch syndrome: A case report - Fischerova, Daniela; Scovazzi, Umberto; Sousa, Natacha; Hovhannisyan, Tatevik; Burgetova, Andrea; Dundr, Pavel; Němejcová, Kristýna; Bennett, Rosalie; Vočka, Michal; Frühauf, Filip; Kocian, Roman; Indrielle-Kelly, Tereza; et al. (Frontiers in Oncology, 2023)
We report a rare case of primary nodal, poorly differentiated endometrioid carcinoma associated with Lynch syndrome. A 29-year-old female patient was referred by her community gynecologist for further imaging with suspected right sided ovarian endometrioid cyst. Ultrasound examination by an expert sonographer at tertiary center revealed unremarkable findings in the abdomen and pelvis apart from three iliac lymph nodes showing signs of malignant infiltration in the right obturator fossa and 2 lesions in the 4b segment of the liver. During the same appointment ultrasound guided tru-cut biopsy was performed to differentiate hematological malignancy from carcinomatous lymph node infiltration. Based on the histological findings of endometrioid carcinoma from lymph node biopsy, primary debulking surgery including hysterectomy and salpingo-oophorectomy was performed. Endometrioid carcinoma was confirmed only in the 3 lymph nodes suspected on the expert scan and primary nodal origin of endometroid carcinoma developed from ectopic Müllerian tissue was considered. As a part of the pathological examination immunohistochemistry analysis for mismatch repair protein (MMR) expression was done. The findings of deficient mismatch repair proteins (dMMR) led to additional genetic testing which revealed deletion of the entire EPCAM gene up to exon 1-8 of the MSH2 gene. This was unexpected considering her insignificant family history of cancer. We discuss the diagnostic work-up for patients presenting with metastatic lymph node infiltration by cancer of unknown primary and possible reasons for malignant lymph node transformation associated with Lynch syndrome.